P477 Two cases of late onset GBS Infection despite post natal benzylpenicillin administration. (June 2019) - Piggott, Simon; Moylett, Edina; Ryan, Ethel; Riain, Una Ni
Abstract : Aim: Streptococcus agalactiae (Group B streptococcus, GBS) is the leading cause of invasive infection among neonates and young infants in the developed world. The prevention of late onset GBS disease (LOD) remains elusive. We present two cases of LOD, one near fatal with significant morbidity, despite early treatment with benzylpenicillin in each case. Method: Following confirmation of GBS LOD, the medical record for each infant was reviewed at University Hospital Galway. Relevant clinical and laboratory information was recorded. Results: Case 1, following an intrapartum high vaginal swab positive for GBS with a clinical suspicion for chorioamnionitis at time of delivery, an otherwise well infant (born at 28+6 weeks) was treated empirically with a 5 day course of IV benzylpenicillin and gentamicin despite sterile blood cultures. The infant's neonatal intensive care unit (NICU) course was uneventful until day of life (DOL) 25 when following a clinical deterioration necessitating a sepsis evaluation, the infant's blood culture isolated GBS, the infant made a full recovery. Case 2, a singleton female infant (born at 31+6 weeks) was treated empirically with a 48 hour course of IV benzylpenicillin and gentamicin owing to an intra-uterine death of unknown cause at 18 weeks during a triplet pregnancy. There were no positive swabs/clinical suspicion for intra-partum infection with neonatal sterile blood cultures following delivery. Standard NICU care was carried out until DOL 9 when the infant developed overwhelming sepsis with GBS positive blood cultures and was transferred to a tertiary NICU centre for further care. The infant survived with significant morbidities. In both of our cases, multi-locus sequence typing and serotyping allowed accurate identification of isolates. Our chosen cases demonstrate the continued prevalence of GBS and the recognised limitations of prophylactic antibiotic use with both of the infants developing GBS infection between days 7–89 of life despite initial antibiotic administration. Conclusion: Antenatal risk-based guidelines and antibiotic prophylaxis are effective in ameliorating early onset GBS infection but are inadequate for combating LOD. Admittedly, the pathogenesis of LOD remains elusive and the route of acquisition is still unclear, possibly vertically from mother or horizontally from environmental sources. Our cases support each of these theories. Postnatal antibiotic therapy does not protect against LOD highlighting the potential role for vaccination in LOD prevention.